Pengaruh Pengelolaan Sarana Prasarana Bimbingan Dan Konseling Terhadap Layanan Bimbingan Karier Peserta Didik Kelas Xii Di Madrasah Aliyah Negeri 2 Karawang - Rahmawati, Rahmawati; Fahmi, Ilham; Faizin, Muhamad (Jurnal Ilmiah Wahana Pendidikan, 2025)
This research discusses career guidance services at Madrasah Aliyah Negeri 2 Karawang and how the management of guidance and counseling facilities and infrastructure influences these services. The research background shows that the existing facilities and infrastructure are inadequate, so that the guidance and counseling room cannot guarantee students' privacy. This research aims to determine the planning, procurement, utilization, maintenance and supervision of guidance and counseling infrastructure in the implementation of career guidance services. The method used is a descriptive method with a quantitative approach and an ex-post facto type of research. The research population consisted of all 134 class XII students, and data collection techniques included questionnaires, observation and documentation with Likert scale instruments. The research results show that the management of guidance and counseling infrastructure is in the medium category with a score of 58%, while student career guidance services are also in the medium category with a score of 82%. There is a significant influence between the management of guidance and counseling infrastructure on career guidance services for class XII students at Madrasah Aliyah Negeri 2 Karawang.